PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS MULTIREPRESENTASI PADA PEMBELAJARAN FISIKA DI SMA/MA - Tegas Amanda Setyandaru; Sri Wahyuni; Pramudya Dwi aristya Putra (FKIP Universitas Jember, 2017)
This research purpose was to create a new product in the form of multi-representation based module that can be used in learning activities. Multi-representation based module was an interesting module that made students understand the material easily. The purpose of this research was to produce a valid multi-representation based modules, to describe the students’ multi-representation ability and to know the students' response to the use of multi-representation based modules. The research design used the 4-D model that was reduced to be 3-D. The results of the research showed that the multi-representation based module was categorized quite valid with the value of expert validation was 3.89. Multi-representation capability on high criteria with N-gain value is 0.75. Meanwhile, the student's response was in the positive response category with the value of 79.4%. Multi-representation based module contained verbal representation, mathematical, pictures and graphs that were useful to help students to understand the material. Based on the results of this research, it could be concluded that the multi-representation based module was suitable to use as an interesting learning module. Keyword: multirepresentation based module logic, validity, multirepresentation ability, student response